Mobile Simulation-Based Learning (MSBL): An Integrated Approach to Enhance Hands-On Instruction in Studying Basic Electronics - Capao, Mafet; Rosales, Victor; Leuterio, Jan Vincent; Baldonado, Faith; Requino, Roque (Journal of Technical Education and Training, 2025)
Technology integration in technical and vocational education has gained attention as educators seek innovative methods to enhance learning effectiveness. This study investigates the effectiveness of integrating Mobile Simulation-Based Learning (MSBL) with traditional hands-on laboratory instruction in enhancing students’ learning performance in Basic Electronics. A quasi-experimental mixed-methods approach with a pretest-posttest control group design was employed, involving 40 higher education students. Learning performance was assessed using researcher-developed multiple-choice tests, while semi-structured interviews captured students’ perceptions. Results indicated significant improvement in learning outcomes for both groups; however, the experimental group showed a notably greater increase in scores (mean gain = 9.10) compared to the control group (mean gain = 6.85). This suggests that MSBL uniquely facilitates deeper conceptual understanding and practical skill acquisition due to its accessibility, interactive nature, and seamless integration with physical laboratory experiences. Students reported increased flexibility, enhanced metacognitive awareness, and a smoother transition between theoretical and practical learning environments. Practically, this study underscores the scalability and effectiveness of MSBL compared to traditional digital tools, offering institutions a more adaptable and cost-effective approach to delivering technical education. The findings recommend systematic MSBL integration into TVET curricula and specialized instructor training for optimal implementation, ultimately improving students’ competency and industry readiness.